Integrated Digital Marketing Strategy for UMKM in Facing Globalisation Challenges : A Multi-Channel and Digital Alliance Approach - Adi Hermawansyah; Sudarmiatin Sudarmiatin (International Forum of Researchers and Lecturers, 2025)
The development of digitalisation and globalisation requires MSMEs to adopt effective and integrated digital marketing strategies to improve competitiveness in international markets. This study aims to examine the effect of an integrated digital marketing strategy, which combines multi-channel and digital alliance approaches, on MSME performance. A quantitative research method with a survey approach was used, involving a sample of MSMEs that have been actively using digital marketing for at least six months. Data were analysed using Structural Equation Modeling (SEM) with the help of AMOS software. The results showed that multi-channel integration and digital alliances significantly improved the marketing performance of MSMEs in facing the challenges of globalisation. The findings strengthen the Resource-Based Theory (RBT) and Technology Acceptance Model (TAM) in the context of MSME digital marketing. The practical implications of this research emphasise the importance of digital capability development and strategic collaboration as keys to the success of MSMEs in the global market. The research also provides recommendations for MSME players and policy makers to support training programmes and facilitation of sustainable digital alliances.